Virtual Reality Laboratories in Engineering Blended Learning Environments: Challenges and Opportunities - Marina Brancaccio; Domenica Mirauda; Salvatore Patera; Ugo Erra (Je-LKS: Journal of E-Learning and Knowledge Society, 2024)
A great number of educational institutions worldwide have had their activities partially or fully interrupted following the outbreak of the COVID-19 pandemic. Consequently, universities have had to take the necessary steps in order to adapt their teaching, including laboratory workshops, to a fully online or mixed mode of delivery while maintaining their academic standards and providing a high-quality student experience. This transition has required, among other efforts, adequate investments in tools, accessibility, content development, and competences as well as appropriate training for both the teaching and administrative staff. In such a complex scenario, Virtual Reality Laboratories (VRLabs), which in the past already proved themselves to be efficient tools supporting the traditional practical activities, could well represent a valid alternative in the hybrid didactic mode of the contemporary educational landscape, rethinking the educational proposal in light of the indications coming from the scientific literature in the pedagogical field. In this context, the present work carries out a critical review of the existent virtual labs developed in the Engineering departments in the last ten years (2010-2020) and includes a pre-pandemic experience of a VRLab tool - StreamFlowVR - within the Hydraulics course of Basilicata University, Italy. This analysis is aimed at highlighting how ready VRLabs are to be exploited not only in emergency but also in ordinary situations, together with valorising an interdisciplinary dialogue between the pedagogical and technological viewpoints, in order to progressively foster a high-quality and evidence-based educational experience.